2019
DOI: 10.1162/ajhe_a_00112
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Graduation Requirements on Risky Health Behaviors of High School Students

Abstract: for their helpful comments. All errors are ours alone. The corresponding author is Benjamin Cowan. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…In these and other prevalent decisions, the risk attitude of an individual can be expected to play a major role. 3 Prior literature suggests that individuals' risk taking preferences are not constant, but can be influenced by various exogenous factors (Hao and Cowan 2019;Browne et al 2019Browne et al , 2021Guiso and Paiella 2008;Menkhoff et al 2006). We add to this literature by expanding this list of factors that change risk preferences by mental health changes.…”
Section: Motivationmentioning
confidence: 99%
“…In these and other prevalent decisions, the risk attitude of an individual can be expected to play a major role. 3 Prior literature suggests that individuals' risk taking preferences are not constant, but can be influenced by various exogenous factors (Hao and Cowan 2019;Browne et al 2019Browne et al , 2021Guiso and Paiella 2008;Menkhoff et al 2006). We add to this literature by expanding this list of factors that change risk preferences by mental health changes.…”
Section: Motivationmentioning
confidence: 99%
“…11,12 Observational studies have found that students who complete their education without a high school diploma have worse health outcomes in adulthood across a wide spectrum of acute and chronic diseases, such as heart disease, cancer, obesity, and human immunodeficiency (HIV) infection. 13,14 Greater investments in education and more school rigor is linked to better health, particularly among low-income and minority populations, 15,16 and experimental and quasi-experimental studies suggest the impact of education on health is causal. [17][18][19][20] Obtaining a high school diploma is the gateway to higher education, employment opportunities, and socioeconomic success.…”
Section: The Importance Of Adolescencementioning
confidence: 99%
“…Students who work harder at school may be less likely to engage in such behaviors and vice-versa. There is broad evidence that human capital investment reduces risky behavior (Conti, Heckman, and Urzua, 2010;Cutler and Lleras-Muney, 2010;Kenkel, Lillard, and Mathios, 2006), as well as evidence that the stringency of education dampens risky behaviour (Hao and Cowan, 2019). This could be explained by time constraints in case of contemporaneous e ects as well as expectation e ects, if students anticipate the future cost of engaging in risky behaviour in terms of reduced return to human capital.…”
Section: Measures Of E Ort: Risky Behaviorsmentioning
confidence: 99%